People Overestimate Their Willingness to Reject Potential Romantic Partners by Overlooking Their Concern for Other People. (December 2014) - Joel, Samantha; Teper, Rimma; MacDonald, Geoff
Mate preferences often fail to correspond with actual mate choices. We present a novel explanation for this phenomenon: People overestimate their willingness to reject unsuitable romantic partners. In two studies, single people were given the opportunity to accept or decline advances from potential dates who were physically unattractive (Study 1) or incompatible with their dating preferences (Study 2). We found that participants were significantly less willing to reject these unsuitable potential dates when they believed the situation to be real rather than hypothetical. This effect was partially explained by other-focused motives: Participants for whom the scenario was hypothetical anticipated less motivation to avoid hurting the potential date's feelings than participants actually felt when they believed the situation to be real. Thus, other-focused motives appear to exert an influence on mate choice that has been overlooked by researchers and laypeople alike.